An investigation of United States federal policy attempts to reduce American Indian and Alaska Native disaster vulnerability - Carter, Lucy, author; Peek, Lori, advisor; Unnithan, N. Prabha, committee member; Trumbo, Craig, committee member (Colorado State University. Libraries, 2016)
To view the abstract, please see the full text of the document.